Are corticosteroid injections more beneficial than anaesthetic injections alone in the management of rotator cuff-related shoulder pain? A systematic review. Issue 8 (5th January 2018) - Cook, Tim; Minns Lowe, Catherine; Maybury, Mark; Lewis, Jeremy S
Abstract : Objective: To compare the effectiveness of corticosteroid injections to local anaesthetic injections in the management of rotator cuff-related shoulder pain (RCRSP). Design: Systematic review with best evidence synthesis. Data sources: The Cochrane, PubMed, CINAHL Plus, PEDro and EMBASE electronic databases were searched (inception until 8 June 2017). Reference lists of included articles were also hand searched. Eligibility criteria: Two reviewers independently evaluated eligibility. Randomised controlled trials (RCTs) were included if they compared subacromial injections of corticosteroid with anaesthetic injections. Two reviewers independently extracted data regarding short-term, midterm and long-term outcomes for pain, self-reported function, range of motion and patient-perceived improvement. Results: Thirteen RCTs (n=1013) were included. Four trials (n=475) were judged as being at low risk of bias. Three studies of low risk of bias favoured the use of corticosteroid over anaesthetic-only injections in the short term (up to 8 weeks). There was strong evidence of no significant difference between injection types in midterm outcomes (12–26 weeks). There was limited evidence of no significant difference between injection types in long-term outcomes. Conclusion: Corticosteroid injections may have a short-term benefit (up to 8 weeks) over local anaesthetic injections alone in the management of RCRSP. Beyond 8 weeks, there was no evidence to suggest a benefit of corticosteroid over local anaesthetic injections. Trial registration number: PROSPERO CRD42016033161.